Answer:
![ax^5+ by^5=241](https://img.qammunity.org/2023/formulas/mathematics/high-school/d8ujzot1jd1kk6uce6enf2h68ra7x29w7w.png)
Explanation:
Given:
We can re-write the left sides of the given equations as follows:
![ax^2+ by^2=(ax+by)(x+y)-xy(a+b)](https://img.qammunity.org/2023/formulas/mathematics/high-school/v0gmtcm8j0fiu661ych1tyjzcg86x0ivlj.png)
![ax^3+ by^3=(ax^2+by^2)(x+y)-xy(ax+by)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vozurhy2fjakx0ehgwbhlkfg58k7crgsgy.png)
![ax^4+ by^4=(ax^3+by^3)(x+y)-xy(ax^2+by^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/oey9pbb0a3j51kxb2lvvj6rkvklmp80s3h.png)
Therefore, following this pattern:
![ax^5+ by^5=(ax^4+by^4)(x+y)-xy(ax^3+by^3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/tfa71yl8b7a2gtbeaj4q7fgephnzri1d5s.png)
Use the given values and the expanded expressions to create 2 equations to help find the values of (x+y) and xy:
Equation 1
![ax^3+ by^3=(ax^2+by^2)(x+y)-xy(ax+by)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vozurhy2fjakx0ehgwbhlkfg58k7crgsgy.png)
![\implies 25=11(x+y)-xy(1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/nmdj2gy8t77o5w3x9294b2qzwhuvtf2zve.png)
![\implies 25=11(x+y)-xy](https://img.qammunity.org/2023/formulas/mathematics/high-school/ojvxh7ox4i6cxpfj2nvqi1e5c6gnms0sxu.png)
Equation 2
![ax^4+ by^4=(ax^3+by^3)(x+y)-xy(ax^2+by^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/oey9pbb0a3j51kxb2lvvj6rkvklmp80s3h.png)
![\implies 83=25(x+y)-xy(11)](https://img.qammunity.org/2023/formulas/mathematics/high-school/on9liqwxzwd0wpfv5tl09qykk0vyrq6plu.png)
![\implies 83=25(x+y)-11xy](https://img.qammunity.org/2023/formulas/mathematics/high-school/b5wg41sy3x5uajowjvspwfkng8artv8n8g.png)
Multiply Equation 1 by 11:
![\implies 275=121(x+y)-11xy](https://img.qammunity.org/2023/formulas/mathematics/high-school/zv2gn12lgpwo04j5inm7h0vwm1il55is5p.png)
Then subtract Equation 2 from this to eliminate 11xy and find the value of (x+y):
![\implies 192=96(x+y)](https://img.qammunity.org/2023/formulas/mathematics/high-school/rh7wg4mwrz808zdfz6fe4fw3da1db0gij3.png)
![\implies (x+y)=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/gwfrne48zbja7s1dzwvljr6okm31vpot5y.png)
Multiply Equation 1 by 25:
![\implies 625=275(x+y)-25xy](https://img.qammunity.org/2023/formulas/mathematics/high-school/xetipc10xwfawnaavo7c0kf7l44io49kv8.png)
Multiply Equation 2 by 11:
![\implies 913=275(x+y)-121xy](https://img.qammunity.org/2023/formulas/mathematics/high-school/pu4np77mgbzdxkpbsap2ce5ihz8yhtzw4b.png)
Subtract the 2nd from the 1st to eliminate 275(x+y) and find the value of xy:
![\implies 288=-96xy](https://img.qammunity.org/2023/formulas/mathematics/high-school/bii8f5b4oq5crrii8dzr09a1172cwm397k.png)
![\implies xy=-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/xna7unmkgugku8214q36g027jf7yz81ngr.png)
Therefore, we now have:
Substitute these into the equation for ax⁵ + by⁵ and solve:
![\implies ax^5+ by^5=(ax^4+by^4)(x+y)-xy(ax^3+by^3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/jpfugue96yc23jw8iaanp6m5937j3dhh36.png)
![\implies ax^5+ by^5=(83)(2)-(-3)(25)](https://img.qammunity.org/2023/formulas/mathematics/high-school/yjzpjisux2ed4oa6yvmxucp52f4nzyl1t7.png)
![\implies ax^5+ by^5=166+75](https://img.qammunity.org/2023/formulas/mathematics/high-school/1vqb244fbwei8hek77zocksb7mkhkijl1f.png)
![\implies ax^5+ by^5=241](https://img.qammunity.org/2023/formulas/mathematics/high-school/st48xku9ljvg5xxbp18n7n7fhidbzx3pl7.png)